Polymeric emulgel carrying Cinnamomum tamala extract: promising delivery system for potential topical applications (Brazilian Journal of Pharmaceutical Sciences, 2020)
Currently, the use of natural compounds obtained from plants tremendously increased due to their promising therapeutic properties. The aim of this study was to formulate a stable emulgel formulation loaded with Cinnamomum tamala (CT) extract. The antioxidant activity of plant extract was determined by DPPH inhibition assay. The extract was successfully loaded into an emulgels using different concentrations of carbopol-940, liquid paraffin, emulsifying agents and preservatives. Preliminary stability study was performed of 17 CT emulgel formulations at accelerated temperature of 50 °C for 2-months. Organoleptic evaluation, centrifugation, globule size, pH, electrical conductivity and rheological studies were performed for a period of 90-days at different temperature including 8, 25, 40 and 40 °C ±75% RH. The CT extract showed promising antioxidant activity of about 81%. On the other hand, the CT loaded emulgel formulation displayed high physical stability at all tested conditions of temperature and time. However, slight decrease in pH and minimum increase in conductivity was observed at 40 and 40 °C±75% RH. The rheological examination of CT emulgel indicated the flow index values of all the samples kept at different temperatures were less than 1, demonstrated non-newtonian and pseudo-plastic nature of CT emulgel. Taken together, the CT emulgel formulation has been evinced to be an excellent addition in the field of topical formulations.